Dynamic Pricing for Perishable Items Considering Substitutes and Advertisement - et. al., Masoud Amini, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study is an attempt to model and solve a pricing model of inventory control model. The literature on this topic is really comprehensive and many different factors including product variety, product perishability, money's temporal value, etc. have been thoroughly studied. Most of these studies are included in literature review section of this paper. The innovation and distinction between this study and those available in the literature is consideration for advertisement as an influential factor which affects demand function. In addition, two different models are studied through considering maintenance costs in two varieties as time-dependent and time-independent. In this model, the demand function will be investigated for two products which are simultaneously on the market. The demand for products is a multi-variate function of products' price and advertisement and timing factors through considering substitution rate. Substitution rate clarifies that a customer can be inclined toward any of the products with different prices. To enhance the applied dimension of this study, advertisement factor (frequency advertisement) has been considered on the one hand and maintenance costs have been considered in two different forms of time-dependent and time-independent on the other. The following section entails a schematic representation of this study. Profit function has been optimized through mathematical modelling of the problem. The main question of this study is selecting an optimal level for the price and advertisement expenses or continuity in pricing problem to maximize the profits obtained by a business in a [0, T] time frame.